Negotiating Islamic Law and Religious Tolerance in Mixed-Marriage Families in South Korea - Whindari, Yayuk; Sudirman, Sudirman; Zulaichah, Siti; Hayati, Irma Nur; Hyun, Park Ji; Taufiqi, Muchammad Zidan (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
The dynamics of mixed-marriage families between Muslims and non-Muslims in South Korea illustrate how Islamic legal principles are negotiated within a multicultural and minority context. This study examines how Indonesian–Korean families practice and reinterpret Islamic law by integrating Social Construction Theory and the maqāṣid al-sharī‘ah framework. This research employs a socio-juridical qualitative design supported by demographic statistics on Indonesian migrants and intermarriages from Korean government sources. Primary data were obtained through in-depth interviews and semi-structured questionnaires with ten purposively selected Indonesian Muslim–Korean couples, while some other data were gathered from the Korean Muslim Federation (KMF) and the Indonesian Muslim Student Association (IMUSKA), both playing a central role in community support and religious education. Data were analysed in three stages: reduction, data display, and conclusion-drawing, to obtain a thematic interpretation that integrates social and legal dimensions. The findings reveal diverse strategies among Muslim spouses in balancing religious obligations with tolerance toward non-Muslim partners and families. Some maintain strict adherence to Islamic prohibitions, while others accommodate local cultural practices such as communal dining or social gatherings involving alcohol, interpreting these as expressions of respect and family harmony rather than religious neglect. These negotiations demonstrate that tolerance within mixed-marriage families is an active, socially constructed process shaped by daily interaction, cultural adaptation, and pragmatic decision-making. From the maqāṣid al-sharī‘ah perspective, such practices can be understood as preserving core objectives of Islamic law—ḥifẓ al-dīn (protection of faith), ḥifẓ al-nasl (family and lineage), and ḥifẓ al-ijtima‘ (social harmony). This research contributes to broader discussions on Islamic law, interfaith relations, and the lived experiences of Muslim minorities, highlighting how Islamic legal principles operate dynamically within non-Muslim communities.